Building blocks from petroleum sludge: Leachability and toxicity studies - Johnson, O.A. (Research India Publications, 2015)
Petroleum sludge is a significant hazardous waste from the petroleum industry; its treatment and disposal have become a global challenge. This paper investigates the leachability and toxicity of this hazardous waste encapsulated in building blocks as an economic useful alternative to disposal. The building block specimens were prepared with different percentages of petroleum sludge (50, 60, 70, and 80 ), and thermally oxidized waste cooking oil was used as a binder. The blocks were subjected to toxicity characteristics leaching tests and its environmental acceptability was evaluated. The results show that the concentration of the PAHs, COD, and heavy metals are within the acceptable level required by the US Environmental Protection Agencyâs (USEPA). Â© Research India Publications 2015.